The Influence of Compensation and Motivation on the Work Productivity of Warehouse Employees at PT Adis Dimension Footwear in Tangerang Regency - Kohari, Syahrul Muhammad; Sukarya, Yaya; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine the extent to which compensation and motivation affect the work productivity of warehouse employees at PT Adis Dimension Footwear in Tangerang Regency.This study used a quantitative descriptive method, which describes variables as they are, supported by numerical data derived from actual conditions. The population in this study was all warehouse employees at PT Adis Dimension Footwear in Balaraja, Tangerang. The research sample consisted of 50 respondents. This study used a saturated sampling technique due to the small population size; therefore, the entire population of 50 employees was used as respondents. Data collection techniques used were observation, questionnaires, and documentation. Data analysis used multiple linear regression analysis with SPSS 26. Data validity was obtained through a partial t-test and a simultaneous F-test.The results of this study indicate that (1) partially, compensation significantly influences the work productivity of warehouse employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (2.638>2.011) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, motivation significantly influences the work productivity of Ware House employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by the calculated t value> t table (4.752>2.011) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, compensation and motivation significantly influence the work productivity of Ware House employees at PT. Adis Dimension Footwear Balaraja-Tangerang, which is indicated by F count> F table (20.388>3.20) with a significance level of 0.000. Thus Ha is accepted and H0 is rejected.Based on the research results, it can be concluded that compensation and motivation variables, both partially and simultaneously, have a significant influence on the work productivity of Warehouse employees at PT. Adis Dimension Footwear Balaraja-Tangerang.